PERAN SERTA ORANG TUA DALAM MENINGKATKAN KETERAMPILAN MEMBACA MENULIS PERMULAAN DENGAN METODE GLOBAL INTUITIF - RIANTO, EDY (Pendidikan Luar Biasa, 2012)
Abstract; This class action research uses global intuitive method and involves the parents of the deaf student on the learning process wheter it is in the school or the house. The purpose of the research are to in crease the students ability of reading and writing and to in crease the parents involment on learning process in the school or the house. On the first cycle, it is found that the students ability of reading and writing sample sentence get 77 % and the parents activity on the involvement of the learning procers is 79,08 %. Based on the result of the first cycle the researcher continued to the action reseach on second cycle, on this cycle the researcherincrease the home visit to the students parents,uses the same age child as contemporary tutor, repair the parents guidance in home. Those three aspect show the result of the study completely, which is more than 80 %. Based of the result of the research, it can be concluded that the result of the beginning of reading and writing ability is better and more increase on the second cycle than the first cycle, especrally on reading the simple sentence the students have written. The parents are also more intensive or involve the their childrens education.